Dysregulated Gene Expression of Imprinted and X-Linked Genes: A Link to Poor Development of Bovine Haploid Androgenetic Embryos - Aguila, Luis; Suzuki, Joao; Hill, Amanda B. T.; García, Mónica; de Mattos, Karine; Therrien, Jacinthe; Smith, Lawrence C. (Frontiers in Cell and Developmental Biology, 2021)
Mammalian uniparental embryos are efficient models for genome imprinting research and allow studies on the contribution of the paternal and maternal genomes to early embryonic development. In this study, we analyzed different methods for production of bovine haploid androgenetic embryos (hAE) to elucidate the causes behind their poor developmental potential. Results indicate that hAE can be efficiently generated by using intracytoplasmic sperm injection and oocyte enucleation at telophase II. Although androgenetic haploidy does not disturb early development up to around the 8-cell stage, androgenetic development is disturbed after the time of zygote genome activation and hAE that reach the morula stage are less capable to reach the blastocyst stage of development. Karyotypic comparisons to parthenogenetic- and ICSI-derived embryos excluded chromosomal segregation errors as causes of the developmental constraints of hAE. However, analysis of gene expression indicated abnormal levels of transcripts for key long non-coding RNAs involved in X chromosome inactivation and genomic imprinting of the KCNQ1 locus, suggesting an association with X chromosome and some imprinted loci. Moreover, transcript levels of methyltransferase 3B were significantly downregulated, suggesting potential anomalies in hAE establishing de novo methylation. Finally, the methylation status of imprinted control regions for XIST and KCNQ1OT1 genes remained hypomethylated in hAE at the morula and blastocyst stages, confirming their origin from spermatozoa. Thus, our results exclude micromanipulation and chromosomal abnormalities as major factors disturbing the normal development of bovine haploid androgenotes. In addition, although the cause of the arrest remains unclear, we have shown that the inefficient development of haploid androgenetic bovine embryos to develop to the blastocyst stage is associated with abnormal expression of key factors involved in X chromosome activity and genomic imprinting.